Implementation of the Village Financial System in Improving Apparatus Performance in Financial Management in Monta Baru Village, Lambu District, Bima Regency - Friansyah, Didin; Yamin, Ahmad; Nuryani, Hanifah Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The village financial system application (siskeudes) is a tool intended for village governments in managing village finances starting from the planning, budgeting, administration and bookkeeping stages. The research objective is to describe the implementation of the Village Financial System in improving the performance of officials in financial management in Monta Baru Village, Lambu District, Bima Regency. This research uses descriptive research with a qualitative approach, data collection techniques through interviews, observation and documentation, with key informants such as the village secretary, village treasurer, Siskeudes operator and BPD chairman. The research results show that there are indicators in answering research problems, namely: 1) There is conformity between implementation and standard implementation procedures. 2) There are sanctions stipulated for errors or negligence in carrying out activities. 3) Existence output and outcome measurable. Implementation of the Village Financial system uses the Charles O Jones Model which includes: Organization, Interpretation and application. Thus, it can be concluded that the implementation of the Siskeudes System includes: Organization, 2) Interpretation, 3) Application. Meanwhile, inhibiting factors are resources and networks or devices.